Liberalization and greenhouse gases emissions in the EU-10 - Gonel, Feride; Aksoy, Tolga; Vardar, Baris Nevzat (EMERALD GROUP PUBLISHING LTD, 2013)
Purpose - The purpose of this paper is to analyze the relationship between liberalization and greenhouse gases (GHGs) emissions in Central and Eastern European countries (CEECs). After their memberships, most of the CEECs have already committed to reducing their GHGs emissions. Although emissions have decreased on average, there is a substantial heterogeneity among the countries. Within the liberalization and integration efforts, increasingly huge amount of foreign direct investment (FDI) has flown to the region. Therefore, the question is whether or not this increase in foreign investment to CEECs is related to the polluting industries. The coincidence of increased FDI and GHGs emission has led us to study the relationship between them. Design/methodology/approach - The paper exploited cross-sectional and time series variation of the data. Findings - The paper found that the polluting FDI is positively associated with GHGs emissions in CEECs. Originality/value - Few previous studies have taken into account FDI and environmental performance together, so the analysis represents a notable contribution to the pollution haven literature.
Keywords: Industry; Sustainable environment; CEECs; Liberalization; Foreign direct investment; Greenhouse gas emissions; Environment; EU; Science & Technology - Other Topics